2017
DOI: 10.17576/jkmjc-2017-3303-15
|View full text |Cite
|
Sign up to set email alerts
|

Online News Production, Consumption and Immediacy: The Remediation Perspective

Abstract: Evidence suggests that media displacement theory has limitation to explain the current development in news industry. This paper turns to the work of Bolter and Grusin on remediation which promotes the idea that old media are being transformed into new digital forms. Anchoring on this idea, this paper offers ways of understanding the processes in which online news sources repurpose print news for digital spaces via remediation. Three processes were identified; (1) borrowing the content and reusing it in a diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 45 publications
0
7
0
2
Order By: Relevance
“…Indeed, displacement theory seems to suggest that the demise of the latter is inevitable. The theory predicts either a reduction in consumption of old media as the consumption of new media increases or the old medium will be replaced by the new medium when overlapping functions appear between them (Newell, Pilotta & Thomas, 2008). Past research found support for time displacement effect such as television displaced by online media for informational function (Kayany & Yelsma, 2000) and online video services reduced the time spent on old video media and non-media activities (Lee, Lee & Kim, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, displacement theory seems to suggest that the demise of the latter is inevitable. The theory predicts either a reduction in consumption of old media as the consumption of new media increases or the old medium will be replaced by the new medium when overlapping functions appear between them (Newell, Pilotta & Thomas, 2008). Past research found support for time displacement effect such as television displaced by online media for informational function (Kayany & Yelsma, 2000) and online video services reduced the time spent on old video media and non-media activities (Lee, Lee & Kim, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…They are also encouraged to present information comprehensively, involving technical skills apart from writing, including how to record images, edit images, display graphics, and process data. These transformation and adaptation are also known as remediation (Bolter & Grusin, 1999;Omar, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lewis, Cushion, and James (2005), Boczkowski (2010), Saltzis (2012), together with Buhl, Günther, and Quandt (2019) relied on content analysis to explore how and what types of the news update are treated and managed within time constraints. Still on the issue of content, Boczkowski (2004) as well as Omar (2017), coining remediation perspective, argue on the importance of creating media products that generate the experience of being there for users when they interact with the news content and the medium.…”
Section: The Culture Of Immediacy As Part Of Digital Technology Adaptationsmentioning
confidence: 99%
“…In the context of journalists working in the digital environment, immediacy has never been so important than before. It is aimed at disseminating information quickly, with no lag between fresh content gathered and produced by news producers to be passed on to audiences or news consumers (Karlsson, 2007;Omar, 2017). At its initial stage, during the early adoption of digital technology by conventional media like newspapers, the ability to update the website was considered to be a defining characteristic of online news as compared to traditional media (Domingo, 2008).…”
Section: Introductionmentioning
confidence: 99%